PELAKSANAAN PEMBELAJARAN SENI RUPA SEBAGAI IMPLEMENTASI KONSEP MERDEKA BELAJAR SISWA KELAS III SDN KUNCIRAN 9 KOTA TANGERANG - Gilang Kusuma Ningrum; Eka Yulyawan Kurniawan; E. Sumadiningrat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of visual arts learning as an application of the Merdeka Belajar concept for third-grade students at SDN Kunciran 9 Tangerang. This qualitative descriptive research uses observation, interviews, documentation, and tests as data collection techniques. The findings show that teachers have implemented principles of Merdeka Belajar such as student-centered learning, differentiation, and flexibility. However, obstacles remain, including limited media, parental involvement, and understanding of the curriculum. Overall, the implementation has been quite effective, supported by the principal and school environment, though improvements are still needed in evaluation and facilities.